A Paradox between LV Mass Regression and Hemodynamic Improvement after Surgical and Transcatheter Aortic Valve Replacement. Issue 1 (4th March 2017) - Kadkhodayan, Ana; Lin, Grace; Popma, Jeffrey J.; Reardon, Michael J.; Little, Stephen H.; Adams, David H.; Marcus, Richard; Henry, Sonia; Baker, Michael T.; Kleiman, Neal S.; Deeb, G. Michael; Huang, Jian; et al.
ABSTRACT: Background: Surgical aortic valve replacement (SAVR) results in higher AV gradients than transcatheter AVR (TAVR), yet calculated left ventricular (LV) mass regresses faster and greater after SAVR vs. TAVR. We examined why LV mass regression is greater after SAVR. Methods: Serial echocardiographic studies of high-risk patients with severe aortic stenosis (AS) randomized to SAVR vs. TAVR with the CoreValve bioprosthesis were analyzed by an echocardiographic core laboratory blinded to treatment and outcomes. Measurements followed established guidelines and LV mass was calculated using the formula of Devereux and colleagues. Results: Echo data were available in 389 TAVR and 353 SAVR patients, whose baseline LVEDD, PWT, SWT, LV mass, and stroke volume (SV) as well as AS severity were similar. At discharge after SAVR, LV mass reduction was significant (227.45 ± 65.02 to 215.08 ± 59.02 g [ p = 0.002]) due to decreased LVEDD (5.01 ± 0.64 to 4.81 ± 0.65 cm [ p < 0.001]) associated with reduced SV (72.6 ± 27.0 mL to 58.9 ± 21.1 mL ( p = 0.015]). PWT and SWT were unchanged. However, after TAVR, all these variables remained similar. At 1 year, LV mass, SV and LVEDD remained smaller following SAVR vs. TAVR. There was a trend toward higher 30-day mortality in patients with greater LV mass reduction in SAVR (4.7% vs. 0.8 %; p = 0.058) which was not observed after TAVR. Conclusion: The greater reduction in LV mass calculated after SAVR vs. TAVR is due to a smaller postoperative LVEDD and is associated with significantly reduced SV. There was a tendency for increased 30-day mortality associated with greater reduction in calculated LV mass after SAVR.